2011
DOI: 10.1111/j.1365-2672.2011.05186.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of cryptococcal pathogenesis and antifungal drugs using a silkworm infection model with Cryptococcus neoformans

Abstract: Aims:  To develop an in vivo system that could quantitatively evaluate the therapeutic effects of antifungal drugs using a silkworm infection model with Cryptococcus neoformans. Methods and Results:  Silkworms reared at 37°C died after an injection of viable serotype A C. neoformans fungus into the haemolymph. The serotype A C. neoformans, which is known to have higher mammal pathogenicity than the serotype D, was also more virulent against the silkworm. Furthermore, the deletion mutants of genes gpa1, pka1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 41 publications
0
75
0
Order By: Relevance
“…At 37°C, C. neoformans grows in the body of silkworms resulting in a killing effect, whereas at 27°C, the fungus does not kill silkworms. The capsule thickness and the overall size of the cell of C. neoformans increase in the silkworm hemolymph at 37°C, where pathogenicity of C. neoformans is exhibited, whereas apparent morphological changes are not observed at 27°C (12). The capsule has been shown to be necessary for pathogenicity of C. neoformans against mammals.…”
Section: Silkworm Fungal Infection Modelmentioning
confidence: 91%
See 3 more Smart Citations
“…At 37°C, C. neoformans grows in the body of silkworms resulting in a killing effect, whereas at 27°C, the fungus does not kill silkworms. The capsule thickness and the overall size of the cell of C. neoformans increase in the silkworm hemolymph at 37°C, where pathogenicity of C. neoformans is exhibited, whereas apparent morphological changes are not observed at 27°C (12). The capsule has been shown to be necessary for pathogenicity of C. neoformans against mammals.…”
Section: Silkworm Fungal Infection Modelmentioning
confidence: 91%
“…We found that strains deficient in the can, gpa1, or pka1 genes, which are required for virulence in C. neoformans against mammals, also showed low pathogenicity against silkworms (12). The product of the can gene is considered to contribute to the pathogenicity in mammals via the calcineurin signaling pathway (22).…”
Section: Identification Of Fungal Genes Responsible For Pathogenicitymentioning
confidence: 99%
See 2 more Smart Citations
“…These methods model the natural infectious process of pathogenic invasion into the epidermis and intestinal tract, which can then cause local infection that may gradually develop into systemic infection (Onfelt et al 2001;Nayduch et al 2013;Wu et al 2014). The injury method mainly used needles to deliver pathogens by piercing the somatic layer or directly injects pathogens into the insect coelom to cause acute infection and rapidly activate the immune response (Matsumoto et al 2012;Singh et al 2014). However, the inevitable mechanical injury caused by this method may affect the experimental results.…”
Section: Discussionmentioning
confidence: 99%